APPROACH TO THE FORMING OF RATIONAL TECHNOLOGY FOR THE EXPORT CARGOES DELIVERY IN SUPPLY CHAIN ON THE PRINCIPLES OF CO-MODALITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this article, we propose an approach to the forming of rational technology for the export cargoes delivery in the supply chain on the principles of co-modality in the context of effective interaction of delivery participants, which allows reducing the costs of all them through the optimal use of resources related to delivery and increasing the competitive advantages of products. Taking into account the strengthening of cooperation between road and rail transport, under modern conditions, combined transport within the international transport corridor is proposed as an alternative option to promote cargo flow in the supply chain. As a result of experimental studies carried out on the basis of the simulation model of the delivery process in the Petri Nets, the time characteristics of technological processes under alternative schemes depending on the input parameters of the model have been determined. A comparative assessment of alternative delivery schemes based on mathematical models has made it possible to establish that the rational scheme for the delivery of export cargo from Ukraine to Germany via the Pan-European Corridor III is the Rolling Highway technology, which ensures compliance with the cargo owner's requirements for delivery time and cost established by the contract. The proposed approach is recommended as a tool for making managerial decisions when planning and organising the delivery of export cargoes from Ukraine to the EU countries in order to effectively manage supply chains by minimising the cost of delivery and environmental damage.